Nonlinear finite element simulations of ice forces on offshore structures - Sand, Björnar (Luleå, 2008)
The present investigation has been devoted to the development of nonlinear finite element simulations by means of obtaining ice forces on structures. The effects of material nonlinearities and friction between ice and structure are taken into account. The key ingredients of the present approach have been described; a realistic representation of the complex constitutive behavior of ice, accurate tracking of contact between the ice and the structure including coulomb friction sliding, and an automatic procedure for computation of buoyancy forces on a partially or completely submerged ice features. A new three-dimensional constitutive model for ice is developed and the formation of crushing and cracking is treated as phase change. In this approach the material changes from being solid ice to a granular material. In the finite element method, phase change is achieved by using element birth and death capabilities. In this manner, the mechanical behavior of ice is approximated from the brittle end and it is treated as a rate- independent, elastic-brittle material. An algorithm for automatic calculation of the buoyancy forces on partially submerged bodies has been developed. This procedure has been implemented into a general finite element to include buoyancy and gravity forces on isoparametric, hexahedral elements. Several realistic examples of ice-structure interactions have been studied to demonstrate the use of the present computational techniques and include ice sheet or multi-year ice ridge interaction with sloping structure, upward and downward bending cones and a cylindrical structure. In the numerical studies presented herein, the structures are considered fixed and rigid. Contact kinematics based on finite sliding is applied to describe precise tracking of contact nodes and surfaces in order to define clear and unambiguous contact conditions. Contact forces can be split into normal and tangential components, the latter being a result of friction that arises as the deformable ice meets and slides along the ...